Flüchtlinge auf dem deutschen Arbeitsmarkt - Alfred Garloff (Wirtschaftsdienst, 2016)
Die jüngste Flüchtlingswelle nach Deutschland ist zwar einmalig. Dennoch gab es bereits in der Vergangenheit große Zuwanderungswellen nach Deutschland. Es lassen sich daher aus früheren Erfahrungen, aber auch aus Erfahrungen anderer Länder, wichtige Lehren ziehen. Über die Arbeitsmarktintegration von Flüchtlingen in Deutschland ist allerdings bisher wenig bekannt. Hier besteht eine Forschungslücke. Die vorliegenden Erkenntnisse deuten darauf hin, dass sich Flüchtlinge nach einiger Zeit recht gut in den Arbeitsmarkt integrieren. – – In 2015, Germany saw an unprecedented wave of refugee arrivals. However, there were also large migrant waves in the past in Germany and in other countries from which we can draw lessons. This article offers a selective literature overview on the integration of migrants and the labour effects of their integration. The literature on refugees is less rich than the literature on migrants generally. A preliminary result is that the integration of refugees takes time but that after a while integration is generally successful. The overall result on labour market effects of migrant integration is that there are no large effects on wages and employment, but that certain groups, such as as low-skilled and previous migrants, can be negatively affected.
Keywords: J15; 330